THE APPLICATION OF RESTORATIVE JUSTICE THROUGH CUSTOMARY INSTITUTIONS AGAINST CHILDREN IN CONFLICT WITH THE LAW IN LHOKSEUMAWE CITY - Budi Bahreisy (NOMOI Law Review, 2022)
The birth of Law No. 11 of 2012 concerning the Criminal Justice System of Children provides strengthening related to the protection of children in Indonesia. This law is what introduces the concept of diversion which aims to provide protection to children who are in conflict with the law, children who are victims of criminal acts, and society in general as a form of transferring the settlement of children's cases from judicial process to proceedings outside criminal justice in order to realize restorative justice.Based onthis background, the formulation of the problem from this study is whether the factors that cause children to conflict with the law in Lhokseumawe City and how the role of indigenous institutions in the Application of Restorative Justice Against Children In Conflict With The Law in Lhokseumawe City. The theory used in this study uses the theory of relative (deterrence), this theory views the prosecution not as retaliation for the perpetrator's mistakes, but as a means of achieving a useful goal to protect society towards prosperity. From this theory emerged the purpose of application as a means of prevention. And the method used is an empirical research method with qualitative shortness. The purpose of this study is to provide knowledge and understanding about the factors that cause children to conflict with the law in Lhokseumawe City and to provide knowledge about the role of indigenous institutions in the Application of Restorative Justice Against Children In Conflict With Law in Lhokseumawe City.Keywords: Restorative Justice, Indigenous Institutions, Children In Conflict With The Law.